Implantes osseointegrados: evolução e sucesso - Faverani, Leonardo Peres [UNESP]; Ferreira, Gabriel Ramalho [UNESP]; Gaetti-Jardim, Ellen Cristina; Okamoto, Roberta [UNESP]; Shinohara, Elio Hitoshi [UNESP]; Assunção, Wirley Gonçalves [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (My University, 2011)
Introduction: The oral rehabilitation with dental implants is a very viable treatment modality for patients. Therefore the discovery of osseointegration, dentistry has reached the trigger with respect to treatment with a high predictability of success. For this various principles, since the surgical protocols, the choice of material and even the technique for the manufacture of implant-supported prosthesis influence a good prognosis for treatment. Objective: Therefore, it is proposed this study a literature review of the fundamentals of osseointegration, explaining the historical and technical parameters of implantology, focusing in what the literature currently is studying with more intensity, the acceleration of osseointegration. Conclusion:well conducted procedures promotes the best aimed success in implantology. Rough surfaces shows great are for implant-bone contact and better mechanical results. The bone quality is fundamental in results foresigh.

Introdução: A reabilitação com implantes osseointegrados é hoje, uma alternativa de tratamento extremamente vantajosa aos pacientes. Deste a descoberta da osseointegração, a odontologia atingiu alta previsibilidade em seus tratamentos. Para tanto diversos princípios, desde os protocolos cirúrgicos, a escolha do material e até a técnica para confecção das próteses implantossuportadas ou implantorretidas, influenciam num bom prognóstico de caso. Objetivo: Sendo assim, é proposta deste trabalho é realizar uma revisão da literatura no tocante aos fundamentos da osseointegração, parâmetros históricos e técnicos da implantodontia. Conclusões: técnicas bem conduzidas promovem a maior previsibilidade de sucesso na implantodontia. As superfícies rugosas apresentam maior área de contato osso-implante e melhores resultados mecânicos. A qualidade óssea é fundamental na previsibilidade do tratamento.
Osseointegrated implants: evolution and success
Keywords: Osseointegration; Prostheses and implants; Mouth rehabilitation; Osseointegração; Próteses e implantes; Reabilitação bucal